Peran Pendidikan Informal dari Orang Tua untuk Membangun Jiwa Entrepreneurship Unggul Pada Anak Usia Dini - Hutagalung, Martha Larasaty (LPPM Institut Pendidikan Nusantara Global, 2025)
Early age entrepreneurship education is often considered unimportant and not taught with special methods. The purpose of this study is to analyse the role of informal education from parents to build children's entrepreneurship spirit at an early age through appropriate methods. This research uses an instrumental case study method with data collection techniques through observation, direct interaction with the sample, and literature study. The research instruments used were parent response questionnaires and interview sheets. The sampling technique used was purposive sampling where the sample consisted of 26 parents with details of 27% fathers and 73% mothers who are running a business and have early childhood with a variation in age 0-8 years. Data from the questionnaire was analysed based on the percentage of parents' responses. The results showed 88.46% of parents had built the entrepreneurship spirit of early childhood, 86.92% of parents had early childhood with superior entrepreneurship character because they were given entrepreneurship-based learning since early childhood, 86.92% of the entrepreneurship spirit of early childhood was influenced by parenting and 77% of parents had used methods in building the entrepreneurship spirit superior early childhood. Based on research results, it can be concluded that informal education from parents has a significant effect on building a superior entrepreneurial spirit in early childhood. This influence can arise from democratic parenting and entrepreneurship learning methods such as exemplary methods and habituation methods applied by parents.